2008
DOI: 10.1373/clinchem.2007.094961
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentration of Heat Shock Protein 27 and Risk of Cardiovascular Disease: A Prospective, Nested Case-Control Study

Abstract: Background: Heat shock protein 27 (HSP27) has been hypothesized to be a potential biomarker of atherothrombosis. However, no prospective studies have yet been performed to investigate the association between HSP27 plasma concentration and incident cardiovascular events among initially healthy individuals. Methods: We evaluated plasma concentrations of HSP27 at baseline among 255 initially healthy participants in the Women’s Health Study who subsequently developed myocardial infarction, ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
2
26
2
Order By: Relevance
“…These results imply that the source of the eHsp25 is not the cardiomyocyte and that treatment with eHsp25 can regulate the production of Hsp25 in the heart. How eHsp25/27 could interact with cardiomyocytes or provide cardioprotection in the heart has not been fully elucidated previously, although the plasma level of eHsp27 was studied as a potential marker of atherosclerosis risk in humans (Vivanco et al, 2005;Kardys et al, 2008). Potential correlations between activation of various surface receptors and Dox-induced cardiac injury have been identified (Nozaki et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results imply that the source of the eHsp25 is not the cardiomyocyte and that treatment with eHsp25 can regulate the production of Hsp25 in the heart. How eHsp25/27 could interact with cardiomyocytes or provide cardioprotection in the heart has not been fully elucidated previously, although the plasma level of eHsp27 was studied as a potential marker of atherosclerosis risk in humans (Vivanco et al, 2005;Kardys et al, 2008). Potential correlations between activation of various surface receptors and Dox-induced cardiac injury have been identified (Nozaki et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…TLR2 has been identified as a receptor for Dox, and its deletion was found to be protective against Dox-induced cardiotoxicity (Nozaki et al, 2004). Independent studies have shown that circulating eHsp25 could interact with TLRs and act as a putative ligand (Kardys et al, 2008). Thus, we hypothesized that enhancing circulating eHsp25 would antagonize Dox by competitive binding to TLR and prevent Dox-induced cardiotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Among related studies are those of Józefowicz-Okonkwo et al (2009), Kardys et al (2008), and Park et al (2006) which are discussed further below: all of these studies have investigated serum Hsp27 antigen concentrations rather than antibody titers. The findings of the first study, which was performed in 62 patients with CAD and 21 healthy controls, implied that plasma Hsp27 concentrations are significantly higher in patients with 2VD or 3VD CAD compared with patients with 1VD CAD or healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the same study, it was stated that the Gensini scale may not reliably predict the extent of myocardial inflammation and ischemia if a collateral circulation is present (Józefowicz-Okonkwo et al 2009). The second study (Kardys et al 2008) had a prospective, nested design and was performed among initially healthy women. No significant association was reported between baseline plasma Hsp27 concentrations and incident cardiovascular events (including non-fatal MI or ischemic stroke and cardiovascular death) during a period of 5.9 years follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Lower circulating HSPB1 serum levels were documented in atherosclerotic coronary arteries and were inversely associated with increasing plaque progression and age. Thus, serum release of HSPB1 seems to have an atheroprotective and potentially an anti-ageing role (Batulan et al 2016;Kardys et al 2008;Lepedda et al 2009;Martin-Ventura et al 2004;Miller et al 2005;Rayner et al 2008). In a mouse model of atherosclerosis, exogenous administration of HSPB1 reduced plaque progression, corroborating its atheroprotective properties and further suggesting a potential therapeutic benefit ).…”
Section: Extracellular Shsps In Cvd and Inflammationmentioning
confidence: 99%